2021
DOI: 10.1103/physrevlett.127.214301
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Dislocation-Induced Topological Modes in a Three-Dimensional Acoustic Topological Insulator

Abstract: The interplay between real-space topological lattice defects and the reciprocal-space topology of energy bands can give rise to novel phenomena, such as one-dimensional topological modes bound to screw dislocations in three-dimensional topological insulators. We obtain direct experimental observations of dislocation-induced helical modes in an acoustic analog of a weak three-dimensional topological insulator. The spatial distribution of the helical modes is found through spin-resolved field mapping, and verifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Signatures of NH topology, such as edge states and EPs, have been observed in mechanical systems as well [39][40][41][42], where at least the right eigenstates can be probed directly [41,42]. In mechanical systems both dislocation and disclination lattice defects have been engineered to probe Hermitian topological phases [46][47][48], by introducing hopping phase modulation of π across the line of missing microwave resonators (playing the role of lattice sites). Besides directly probing right eigenvectors, dislocation modes can also be detected from the zeros of the reflection coefficient [40] or mechanical susceptibility [46].…”
Section: ) 3(b) and 3(c) For H X H Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Signatures of NH topology, such as edge states and EPs, have been observed in mechanical systems as well [39][40][41][42], where at least the right eigenstates can be probed directly [41,42]. In mechanical systems both dislocation and disclination lattice defects have been engineered to probe Hermitian topological phases [46][47][48], by introducing hopping phase modulation of π across the line of missing microwave resonators (playing the role of lattice sites). Besides directly probing right eigenvectors, dislocation modes can also be detected from the zeros of the reflection coefficient [40] or mechanical susceptibility [46].…”
Section: ) 3(b) and 3(c) For H X H Cmentioning
confidence: 99%
“…Recently, NH topological phases have been realized in photonic crystals with gain and/or loss [33][34][35][36][37][38] and in mechanical metamaterials [39][40][41][42]. On these platforms lattice defects have been engineered to probe Hermitian topological phases [43][44][45][46][47][48]. Therefore, our predictions can, in principle, be tested in NH metamaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Topological lattice defects [27] have been extensively studied in electronic systems [138][139][140] and classical systems [141][142][143][144][145][146][147][148] over the past decade. The classification of topological lattice defects depends on the holonomy along a closed path around the defect core [25,149].…”
Section: Topological Defect Statesmentioning
confidence: 99%
“…The dislocations and disclinations are defined as a gauge flux for translational symmetry and rotational symmetry, respectively [28]. Dislocations and disclinations are mainly investigated on honeycomb lattices and square lattices [149], and it has been demonstrated that they can serve as a bulk probe to detect the topological nature which exhibits topological states [139][140][141][142][143][146][147][148][154][155][156] and/or fractional charges [144,145,157,158] in TCIs protected by crystal symmetries. More recently, topological defect states have been proposed in elastic materials [87,[159][160][161], and then we will discuss the related papers.…”
Section: Topological Defect Statesmentioning
confidence: 99%
“…An important extension of this principle applies to specific topological defects, where the existence of topological states hinges on an interplay between the bulk topology of the lattice and the topological charge of the defect [20][21][22][23][24]. Notable examples include topological states bound to vortices [25][26][27][28], dislocations [29][30][31][32], and disclinations [33][34][35][36][37][38].…”
mentioning
confidence: 99%